Studies in floral crops production: effects of root-zone temperature on dahlia growth and optimizing graphical tracks for poinsettia height management - Schneck, Karen Kay (Kansas State University, 2020)
Dahlia (Dahlia xhybrida Hort.) is subject to ‘dahlia decline,’ a phenomenon in which a crop exhibits graying foliage, root decline, and plant death that has reportedly caused partial or total crop loss and has no known initiating factor. We hypothesized that plant exposure to supraoptimal root-zone temperatures (RZT) during production may initiate the decline. Two experiments were conducted to initiate dahlia decline where supraoptimal RZT were applied to 12 different dahlia cultivars in spring 2019 and 2020. Experiment 1 (Exp 1) exposed potted dahlia root-zones to 22, 35, 40, 45, or 50 °C via water-bath. Experiment 2 (Exp 2) evaluated the effects of exposure time (0-, 2-, 4-, or 6-hrs) during elevated RZT (45 °C). Plant and root conditions were rated before treatment and weekly, for three weeks (Exp 2) and four weeks (Exp 1) post-treatment. Neither experiment resulted in the reported dahlia decline. However, Exp 1 root ratings decreased between 40 to 50 °C in several cultivars after treatment. In Exp 2, root ratings decreased in the 2 to 6-hr treatments compared to the control. Several cultivars exhibited an increase in root rating in the final observations, indicating dahlias could recover from a high heat injury and still develop into a potentially marketable plant. Poinsettias [Euphorbia pulcherrima (Willd. ex Klotzsch)] are the leading winter potted flowering crop in North American greenhouse operations. Markets dictate specific height requirements, so growers employ graphical tracking, a technique to monitor crop height development compared to a target range. These target curves were originally developed in the 1990’s using popular cultivars at that time, but updates are needed for modern varieties produced today. The original curve allows for some customization, but there is no guidance on how to adjust the target range based on cultivar vigor. In the S-shaped graphical tracking curve, there are three parts: the lag phase (~two weeks post-pinch), the linear phase (active growth and transition into the reproductive phase), and the plateau phase (bract expansion and color development). This research focuses on providing growers with information based on the growth of modern poinsettia cultivars of ‘Ferrara’, ‘Premium Marble’, ‘J’Adore Pink’, and ‘Christmas Spirit.’ To evaluate the need for curve adjustment, in 2019, these four poinsettia cultivars were grown in four different glass-greenhouses with early and late pinch dates under different temperature regimes, and heights were measured weekly. Heights were analyzed from two weeks after pinch till short-day initiation by finding the slope and intercept of this line which occurred during the linear phase of growth. Slopes are different depending on the cultivar’s vigor, but not based on pinch date. This response indicates that graphical tracking curves would be better suited for growers if they were modified based on cultivar vigor. This adjustment allows for better growth management during the linear phase and may, therefore, assist growers in meeting target heights at the end of production.
Keywords: Dahlia xhybrida; Poinsettia; Euphorbia pulcherrima; Graphical Tracking; Supraoptimal Root Zone Temperatures; Dahlia decline